Assessing ankle instability during a relevé using accelerometers - Hinton-Lewis, C.; Sanderson, A.; Moyle, G. M.; Thiel, D. V. (Journal of Fitness Research, 2016)
Ankle injuries are a common occurrence in classical ballet. Identifying weakness could reduce the possibility of future injury. Two female dancers in an undergraduate dance programme stood in first position with their arms in second position and performed a sequence of relevés. A single accelerometer was attached to the ankle to determine instability during the study. The results indicate that during the holding phase of the relevé the two participants had different patterns, with Participant 2 showing a continuous spike throughout the 5 relevés. This indicates a weakness in the ankles and therefore suggesting that the coaches should.